Attitude towards the use of electronic cigarettes and usage characteristics: izmir sample - Havaçeliği Atlam, Demet; Şaşman Kaylı, Derya; Yararbaş, Görkem (Journal of Dependence, 2020)
Objective: The aim of this study was to evaluate the electronic cigarette use characteristics of the society and attitude towards e-cigarette. Method: This is a cross-sectional field study conducted face to face in Izmir. The sample size was calculated as 369. 7 districts were determined by lot method. 353 volunteers were reached. The questionnaire form prepared by the researchers was filled out. Results: 19% of the participants declared that they used e-cigarette at least once in their lifetime. In the attitude towards e-cigarettes, smoking characteristics, information source, social environment and perspective are seen as determinants. Gender specific features did not differ in attitude towards ecigarette. Just, women think that e-cigarettes cause passive smoking compared to men. People who use e-cigarettes think e-cigarette is less harmful than traditional cigarette. E-cigarette is preferred more frequently by people who use traditional cigarette, especially dual use comes to the fore. Another situation is that, those who quit smoking prefer e-cigarettes. Because e-cigarettes are seen as an alternative to get rid of cigarette addiction. Conclusion: The results of research are expected to guide the shaping of the community’s attitude towards e-cigarettes, preventive activities and treatment services to be planned for the society.